IMPLEMENTASI KEBIJAKAN PENYELENGGARAAN PENDIDIKAN INKLUSIF PADA SEKOLAH DASAR DI KABUPATEN ACEH UTARA - Naslawati Naslawati; Hera Yanti; Siraj Siraj (Hijri, 2025)
This study aims to analyze the implementation of inclusive education policy in elementary schools in North Aceh District, focusing on four key aspects: communication, resources, implementers' disposition, and bureaucratic structure. The research employed a qualitative method with a case study approach, involving data collection through in-depth interviews, observation, and document analysis. The subjects consisted of nine key informants, including officials from the Education Office, school principals, special education teachers, homeroom teachers, and school committee members from two inclusive elementary schools. The findings reveal that the implementation of the inclusive education policy still faces various challenges. Communication among stakeholders is not yet optimal, resources such as teaching personnel and facilities are still limited, the disposition of policy implementers is not supported by an adequate system, and the bureaucratic structure lacks proper coordination. The study identifies that the ineffectiveness of policy implementation is caused by a lack of socialization, training, incentives, and the fragmentation among schools. The study concludes that stronger policy integration, improved resource capacity, and reinforced bureaucratic structures are needed to achieve a high-quality and sustainable inclusive education system